2012
DOI: 10.1097/mpg.0b013e3182575f9c
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Sequential and Standard Therapy for Helicobacter pylori Eradication in Children and Investigation of Clarithromycin Resistance

Abstract: Sequential therapy seems highly effective for eradicating H pylori in children; however, the difference between 2 groups in resistant strains was the limitation of the study. Our country needs to reassess the effectiveness of standard triple therapy regimen for H pylori eradication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 26 publications
(41 reference statements)
2
23
0
1
Order By: Relevance
“…In a study by Zullo et al, [12] eradication rates for the sequential therapy were 92% by intent to treat and 95% per protocol. A recent study from Turkey [15] found that the eradication rate was higher for sequential therapy (93.7%) than standard therapy (46.4%). These findings are similar to the findings in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Zullo et al, [12] eradication rates for the sequential therapy were 92% by intent to treat and 95% per protocol. A recent study from Turkey [15] found that the eradication rate was higher for sequential therapy (93.7%) than standard therapy (46.4%). These findings are similar to the findings in our study.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] As shown in Figure 1a, 14-day sequential therapy eradicated the bacterium in 433 of 479 patients in an intention-to-treat analysis, with a pooled success rate of 90.4% [95% confidence interval (CI) 87. .0%].…”
mentioning
confidence: 99%
“…[3][4][5] We did a systemic review of randomised control trials comparing 10 and 14 days as first-line treatment in adults, and identified four randomised trials comparing the efficacy of 10-day and 14/15-day sequential therapies. 4,[6][7][8] Meta-analysis of the four studies showed that 14/ 15-day sequential therapy was not significantly superior to 10-day sequential therapy [risk ratio 1.03, 95% confidence interval (CI) 0.96-1.12, P = 0.418; heterogeneity: Q = 4.2, I 2 = 28.6%, P = 0.241, Figure 1] using a random effects model. The risk difference was 3% (95% CI À3% to 9.1%, P = 0.369).…”
mentioning
confidence: 99%
“…A small study from Turkey indicated that sequential treatment with metronidazole-based regimen might be effective in children, especially in those who are sensitive to clarithromycin (18). However, by using the same regimen, a novel study from Turkey including 113 children, did not show any superiority of sequential treatment over standard therapy (19).…”
Section: Discussionmentioning
confidence: 99%